Analysis of factors influencing accountability for village fund management in 2024 - wanda, wanda; Patra, A. Dahri Adi; Ramadhan, Abid (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the influence of apparatus competence, organizational commitment, and the utilization of information technology on the accountability of village fund management in Belopa District, Luwu Regency. Methodology: The study employs a quantitative approach using multiple linear regression analysis. Data were collected through structured questionnaires distributed to village officials from five villages in Belopa District. Results: The results indicate that organizational commitment and the utilization of information technology have a positive and significant effect on village fund management accountability. In contrast, apparatus competence shows a negative effect on accountability. Novelty: This study introduces an empirical perspective by revealing a counterintuitive relationship between apparatus competence and accountability in village fund management. Findings: Organizational commitment and effective use of information technology emerge as key drivers in enhancing accountability at the village level, while competence alone does not necessarily guarantee better governance outcomes. Originality: The originality of this research lies in its focus on village-level public finance management and its empirical evidence from a rural Indonesian context. Conclusions: Strengthening organizational commitment and optimizing information technology utilization are crucial strategies to improve village fund accountability, alongside the need to reassess competency development programs. Type of Paper: Empirical Research Paper.